2019
DOI: 10.4269/ajtmh.18-0333
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Livestock Feces and Water Quality, Sanitation, and Hygiene (WASH) Conditions among Caregivers and Young Children: Formative Research in Rural Burkina Faso

Abstract: . Livestock farming is common in low-income settings as a source of income and animal-sourced food. However, there is growing evidence of the harmful health effects of proximity of animals to infants and young children, especially through exposure to zoonotic pathogens. Poultry ownership is almost universal in rural Burkina Faso. Poultry feces are a significant risk factor for enteric diseases that are associated with child undernutrition. To investigate the extent of exposure to livestock feces amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Mothers' and children's hands were generally observed to be visibly dirty during the observation periods. These findings confirm the more qualitative results uncovered in formative research undertaken as part of the SELEVER study, where it was found that handwashing was rare for mothers, even after toileting and after disposal of animal faeces, and for children (Ngure et al, 2019). That research also found that children's faeces were also often ignored for long periods after defecation.…”
Section: Status Of Child Nutrition Household Wash Environment Pousupporting
confidence: 85%
“…Mothers' and children's hands were generally observed to be visibly dirty during the observation periods. These findings confirm the more qualitative results uncovered in formative research undertaken as part of the SELEVER study, where it was found that handwashing was rare for mothers, even after toileting and after disposal of animal faeces, and for children (Ngure et al, 2019). That research also found that children's faeces were also often ignored for long periods after defecation.…”
Section: Status Of Child Nutrition Household Wash Environment Pousupporting
confidence: 85%
“…Beyond six months of age critical developmental stages of weaning and crawling mean infection risk increases, [51] with obvious implications for short-and long-term growth and development. However, the evidence base describing the links between domestic animal ownership (particularly chickens), WASH facilities and use and infant nutritional status is limited to a few observational studies [27,[52][53][54][55], which have not consistently measured Campylobacter carriage and/or infection. There is insufficient evidence to fully describe the extent to which infection is caused by exposure to domestic animals in low-and middle-income countries, and furthermore, if infant nutritional status affects whether infection is clinical or subclinical.…”
Section: Competing Interestsmentioning
confidence: 99%
“…Children can be exposed to Campylobacter spp. directly or indirectly through exposure to animal feces (6).…”
Section: Introductionmentioning
confidence: 99%